Oxidative 3,3,3-trifluoropropylation of arylaldehydes - Ikeda, Akari; Omote, Masaaki; Nomura, Shiho; Tanaka, Miyuu; Tarui, Atsushi; Sato, Kazuyuki; Ando, Akira (Beilstein Journal of Organic Chemistry, 2013)
A reaction between (E)-trimethyl(3,3,3-trifluoroprop-1-en-1-yl)silane (1) and arylaldehydes 2 was triggered by fluoride anions to afford aryl 3,3,3-trifluoropropyl ketones 3 in moderate to good yield. A mechanistic study of this reaction indicated that it occurred via an allyl alkoxide (4). A subsequent 1,3-proton shift of the benzylic proton of 4 forms 3. This reaction involves oxidative 3,3,3-trifluoropropylation of an arylaldehyde to afford 4,4,4-trifluoro-1-arylbutan-1-one.
Keywords: cesium fluoride; organo-fluorine; 1,3-proton shift; trifluoromethyl; 3,3,3-trifluoropropenyl

(untitled) - Tomaschenko, O. A.; Grushin, V. V. (Chem. Rev., 2011)

Fluorine in Medicinal Chemistry and Chemical Biology - Yamazaki, T.; Taguchi, T.; Ojima, I. (Unique Properties of Fluorine and Their Relevance to Medicinal Chemistry and Chemical Biology, 2009)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

Modern Fluoroorganic Chemistry: Synthesis, Reactivity, Applications - Kirsch, P. (Wiley-VCH, 2004)

Organofluorine Chemistry, Principles, and Commercial Applications - Hiyama, T. (Springer, 1994)

(untitled) - Prakash, G. K. S.; Yudin, A. K. (Chem. Rev., 1997)

(untitled) - Prakash, G. K. S.; Krishnamurti, R.; Olah, G. A. (J. Am. Chem. Soc., 1989)

(untitled) - Shibata, N.; Mizuta, S.; Kawai, H. (Tetrahedron: Asymmetry, 2008)

(untitled) - Ma, J.-A.; Cahard, D. (J. Fluorine Chem., 2007)

(untitled) - Kobayashi, Y.; Kumadaki, I. (Tetrahedron Lett., 1969)

(untitled) - Oishi, M.; Kondo, H.; Amii, H. (Chem. Commun., 2009)

(untitled) - Cho, E. J.; Senecal, T. D.; Kinzel, T.; Zhang, Y.; Watson, D. A.; Buchwald, S. L. (Science, 2010)

(untitled) - Mizutani, K.; Yamazaki, T.; Kitazume, T. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Yamazaki, T.; Mizutani, K.; Kitazume, T. (J. Org. Chem., 1995)

(untitled) - Konno, T.; Chae, J.; Kanda, M.; Nagai, G.; Tamura, K.; Ishihara, T.; Yamanaka, H. (Tetrahedron, 2003)

(untitled) - Chen, Q.; Qiu, X.-L.; Qing, F.-L. (J. Fluorine Chem., 2007)

(untitled) - Jiang, Z.-X.; Qin, Y.-Y.; Qing, F.-L. (J. Org. Chem., 2003)

(untitled) - Xiong, Z.; Qiu, X.-L.; Huang, Y.; Qing, F.-L. (J. Fluorine Chem., 2011)

(untitled) - Hanamoto, T.; Hakoshima, Y.; Egashira, M. (Tetrahedron Lett., 2004)

(untitled) - Chen, X.-Y.; Qiu, X.-L.; Qing, F.-L. (Tetrahedron, 2008)

(untitled) - Yamazaki, T.; Ichige, T.; Kitazume, T. (Org. Lett., 2004)

(untitled) - Watanabe, Y.; Yamazaki, T. (J. Org. Chem., 2011)

(untitled) - Yamazaki, Y.; Yamamoto, T.; Ichihara, R. (J. Org. Chem., 2006)

(untitled) - Yamazaki, T.; Kawasaki-Takasuka, T.; Furuta, A.; Sakamoto, S. (Tetrahedron, 2009)

(untitled) - Konno, T.; Moriyasu, K.; Ishihara, T. (Synthesis, 2009)

(untitled) - Brisdon, A. K.; Crossley, I. R.; Pritchard, R. G.; Sadiq, G.; Warren, J. E. (Organometallics, 2003)

(untitled) - Brisdon, A. K.; Crossley, I. R. (Chem. Commun., 2002)

(untitled) - Yamazaki, T.; Takita, K.; Ishikawa, N. (J. Fluorine Chem., 1985)

(untitled) - Prakash, G. K. S.; Krishnan, H. S.; Jog, P. V.; Iyer, A. P.; Olah, G. A. (Org. Lett., 2012)

(untitled) - Omote, M.; Tanaka, M.; Ikeda, A.; Nomura, S.; Tarui, A.; Sato, K.; Ando, A. (Org. Lett., 2012)

(untitled) - Omote, M.; Tanaka, M.; Tanaka, M.; Ikeda, A.; Tarui, A.; Sato, K.; Ando, A. (J. Org. Chem., 2013)

(untitled) - Bizet, V.; Pannecoucke, X.; Renaud, J.-L.; Cahard, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Bizet, V.; Pannecoucke, X.; Renaud, J.-L.; Cahard, D. (J. Fluorine Chem., 2013)

(untitled) - Qing, F.; Gao, W. (Chin. J. Org. Chem., 2000)
http://sioc-journal.cn/Jwk_yjhx/EN/abstract/abstract333670.shtml